FEATURES OF THE TOBACCO SMOKING-RELATED RESTRUCTURING OF THE CELLULAR COMPOSITION OF THE ORAL MUCOSA - Hasiuk, N.V.; Yeroshenko, G.A.; Maystruk, P.O. (World of Medicine and Biology, 2018)
The paper presents the findings of the comprehensive morphological study of the oral mucosa in tobacco smokers, obtained during comprehensive and statistic cytological study. The findings specify the described changes as “dyskeratose” or “proliferative” ones, containing cytological criteria for dyskeratosis expressed by impaired keratinization of the epithelium of the anatomic site. The analysis of the proposed patterns of pathogenesis and the existence of common components at its levels, allows to consider the resulted cytological restructuring, namely, “inflammatory” type of the cytograms and “dyskeratose” as two autonomous processes in the oral mucosa induced by tobacco smoking, as well as the levels of the pathogenic mechanism at the stage of pre-tumor transformation.
Keywords: mucous membrane; epithelium; cells; nucleus; cytoplasm